2022
DOI: 10.1186/s13039-022-00620-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of 1q43q44 deletion and corpus callosum malformations: 2 new cases and literature review

Abstract: Background Corpus callosum malformations (CCM) represent one of the most common congenital cerebral malformations with a prevalence of around one for 4000 births. There have been at least 230 reports in the literature concerning 1q43q44 deletions of varying sizes discovered using chromosomal microarrays. This disorder is distinguished by global developmental delay, seizures, hypotonia, corpus callosum defects, and significant craniofacial dysmorphism. In this study, we present a molecular cytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…[3] Subsequent studies, including recent ones, identified over 200 additional patients displaying a broad phenotypic spectrum. [4][5][6][7][8][9] Typical clinical features, including developmental delay, intellectual disability, growth retardation, microcephaly, facial dysmorphisms, and congenital heart defects, have been noted.…”
Section: Hnrnpu-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…[3] Subsequent studies, including recent ones, identified over 200 additional patients displaying a broad phenotypic spectrum. [4][5][6][7][8][9] Typical clinical features, including developmental delay, intellectual disability, growth retardation, microcephaly, facial dysmorphisms, and congenital heart defects, have been noted.…”
Section: Hnrnpu-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…ZNF238 , also known as RP58 encodes a highly conserved (95% homology in the amino acid sequences between humans and mice) transcription factor containing four zinc finger domains (responsible for DNA binding) and a BTB/POZ domain (multifaceted protein–protein interaction motif) (Aoki et al, 1998 ; Tatard et al, 2010 ). Deletion of the distal arm of human chromosome-1q, termed “1qter deletion,” “1q4 deletion,” or “terminal 1q deletion”, is linked to microcephaly with agenesis of the corpus callosum (Boland et al, 2007 ; Hill et al, 2007 ; Bon et al, 2008 ), and the patients carrying this deletion have severe intellectual disability and short stature with profound growth defects (Khadija et al, 2022 ). A critical region contains a handful of genes, including ZNF238 (Boland et al, 2007 ; Hill et al, 2007 ; Bon et al, 2008 ; Orellana et al, 2010 ).…”
Section: Transcription Factors Associated With Microcephalymentioning
confidence: 99%
“…2p25.2 Congenital (Tsurusaki et al, 2014;Hempel et al, 2016;Wakim et al, 2020) Growth deficiency, intellectual disability, characteristic facial features, and hypoplastic nails of the fifth fingers and/or toes Coffin-Siris syndrome Zinc finger ZNF238 * 1q44 Congenital and postnatal (Boland et al, 2007;Hill et al, 2007;Bon et al, 2008;Orellana et al, 2010;Khadija et al, 2022) Severe intellectual disability, profound growth defects, short stature, agenesis of corpus callosum, dysmorphic facial features 1qter deletion syndrome…”
Section: Sox11mentioning
confidence: 99%